2019
DOI: 10.1161/strokeaha.119.027120
|View full text |Cite
|
Sign up to set email alerts
|

Automated Measurement of Cerebral Atrophy and Outcome in Endovascular Thrombectomy

Abstract: Background and Purpose— Methods of identifying ischemic stroke patients with a greater probability of poor outcome following endovascular thrombectomy (EVT) might improve shared treatment decision-making between patients, families, and physicians. We used an objective, automated method to measure cerebral atrophy and investigated whether this was associated with outcome in EVT patients. Methods— Consecutive EVT patients from a single-center registry wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 13 publications
1
24
1
3
Order By: Relevance
“…We would respond that, like Schrödinger's Cat, the skull could be both at the same time. That is, greater intracranial reserve may certainly reflect cerebral atrophy and biologic aging, serving as a marker of impaired resiliency with respect to eventual functional recovery after large-vessel stroke [1]. In parallel but conversely, lower intracranial reserve was a clear marker of higher risk for malignant cerebral edema in our and two other recent studies [2][3][4].…”
supporting
confidence: 66%
“…We would respond that, like Schrödinger's Cat, the skull could be both at the same time. That is, greater intracranial reserve may certainly reflect cerebral atrophy and biologic aging, serving as a marker of impaired resiliency with respect to eventual functional recovery after large-vessel stroke [1]. In parallel but conversely, lower intracranial reserve was a clear marker of higher risk for malignant cerebral edema in our and two other recent studies [2][3][4].…”
supporting
confidence: 66%
“…While atrophy is correlated with age, this imaging surrogate of atrophy was significantly better at distinguishing those destined for malignant edema than age alone. This biomarker, extracted automatically by our image analysis pipeline, has also been demonstrated to predict outcome after endovascular treatment for large-vessel stroke [23]. It likely captures the space available to compensate for swelling and those with more reserve are able to tolerate larger strokes with more edema before deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Furthermore, in AIS patients undergoing MT, cerebral atrophy has been linked to inferior functional outcome. [15] Moreover, brain atrophy is associated with physical frailty, [16,17] and in our previous study we showed that sarcopenia, represented by masseter muscle area and 3 density, is associated with poor three-month survival after MT. [18] The potential predictive value of BAI and its dependence on sarcopenia as well as other risk factors in AIS patients treated with MT remains poorly defined.…”
Section: Introductionmentioning
confidence: 91%